2018
DOI: 10.3168/jds.2017-13917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment of preweaning dairy calves with recombinant bovine somatotropin on immune responses and somatotropic axis

Abstract: Weaning may be associated with negative energy balance and body weight loss when calves are still immunologically immature, predisposing them to infectious diseases. The aim of the present experiment was to investigate the effects of treatment of preweaning dairy calves with recombinant bovine somatotropin (rbST) on the somatotropic axis, selected immune parameters, and hematology of calves around weaning. Thirty-six Holstein female calves were randomly assigned to receive 1.5 to 1.8 mg of rbST (Posilac, Elanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Other authors reported a reduction in the haptoglobin concentration, with the lowest values towards weaning, relating this lesser concentration with lower stress levels [65,66,67]. We probably did not observe this reduction in haptoglobin concentration in our experiment since the last sampling was made a week after the calves were weaned, and the change in feeding, added to the greater consumption of concentrate in that week, could have been responsible for the elevation in the haptoglobin concentration [68].…”
Section: Discussionmentioning
confidence: 54%
“…Other authors reported a reduction in the haptoglobin concentration, with the lowest values towards weaning, relating this lesser concentration with lower stress levels [65,66,67]. We probably did not observe this reduction in haptoglobin concentration in our experiment since the last sampling was made a week after the calves were weaned, and the change in feeding, added to the greater consumption of concentrate in that week, could have been responsible for the elevation in the haptoglobin concentration [68].…”
Section: Discussionmentioning
confidence: 54%
“…Weaning may result in increased Hp concentrations as reported by Belli et al (2018) [41] for calves fed ad libitum and weaned at 7 weeks of age. Hulbert et al (2011) [40] showed that early-weaned calves (45 d) compared with later weaned calves (66 d) had increased plasma concentrations of cortisol and Hp, suggesting that weaning is less stressful when calves are older.…”
Section: Health Status and Hpmentioning
confidence: 87%
“…Ovalbumin-specific antibodies were analyzed using an indirect ELISA ( Ballou and DePeters, 2008 ; Silva et al., 2015 ; Belli et al., 2018 ). A 96-well plate was coated with 100 μL of a 44.04-mM carbonate and 6.04-mM bicarbonate buffer containing 1.4 g/L of ovalbumin and incubated for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The working concentration range was 0.1 to 10 ng/mL and coefficient of variation was 5.4% and 8.7% for intra- and inter-assay, respectively. Since there is no clinical significance for determining protective titers of anti-ovalbumin, data were reported as the average optical density ( OD ) as proof of concept for augmented humoral response (Ballou et al., 2008; Silva et al., 2015 ; Belli et al., 2018 ). Average of the duplicates is reported with the OD of the corresponding blank subtracted.…”
Section: Methodsmentioning
confidence: 99%